Tele-rehabilitation of a middle-aged female with bronchiectasis as post COVID-19 sequelae: a case report - V. Verma, Chhaya; Kamble, Rutuja (International Journal of Research in Medical Sciences, 2022)
COVID-19 pneumonia causes dilatation of lung parenchyma which leads to destruction of segmental bronchi that can further progress into bronchiectasis. COVID-19 causes many sequels in the respiratory system and frequently presents with dyspnoea, fatigue, loss of strength, reduced functional capacity and sometimes severe multi-organ affection. Physiotherapy interventions through tele-rehabilitation have acquired a fundamental role in the recovery of the functions and quality of life. Pulmonary tele-rehabilitation which is done in this case report study includes patient education, respiratory care, exercise training, ambulatory program with supplementary oxygen, strengthening, endurance training and energy conservation. All these interventions play an important role in patent’s treatment protocol from hospital discharge to resuming work by assisting in weaning of supplementary oxygen, improving functional capacity of lungs and thus facilitating recovery. Rehabilitation of COVID-19 causing bronchiectasis in healthy individual has not been reported in literature yet. So, here we present a case report of tele-rehabilitation of a middle- aged female who developed progressive bronchiectasis as a sequela of COVID-19 pneumonia evident on serial chest CT scans.